A jogállamiság fogalmának eszmetörténeti vázlata - Tóth, J. Zoltán (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The present paper aims to briefly review the history of the concept of the rule of law. It gives an account of its three pillars, namely the English rule of law, the French constitutionalism and the German Rechtsstaat, their historically changing meanings and the evolution of the principles they protect. It highlights the political changes in the use of these concepts after the World War II, in an attempt to prevent the Nazi atrocities from recurring, and shows how the rule of law, the Rechtsstaat and the prééminence du droit have been given substance at the end of the 20th and beginning of the 21st century.